Peningkatan Partisipasi Siswa Kelas IV dalam Pembelajaran IPS melalui Media Kartu Di SDN 22 IV Koto Aur Malintang Kabupaten Padang Pariaman - Daswinar Daswinar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Factor that causes student participation under communication in social science study (IPS) still internel study process in teacher, monotonous study, and impress a little stiff, so that make student inclined feel tense and satisfied in learn. potencial student to think, critical, and ask, take outside opinion doesn't bloom well, so to increase student participation in study, teacher be demanded to use strategy that can involve student mobilety. Teacher success in teach doesn't quit of teacher know-how use and choose media and method in study. Watchfulness internal issue formulation how does class student participation enhanced IV in study IPS by using card media at country elementary school. Aim from this watchfulness describes student participation enhanced in study ips pass card media in class IV. country elementary school. Hypothesis that proposed in this watchfulness with card media can be increased class student participation IV in study IPS at country. Watchfulness method that applied class action watchfulness method. Subjek watchfulness class student IV SD. Watchfulness result data student participation data and teacher activity during study in class. In hypothesis testing is used student participation percentage enhanced in study execution in use card media. Data analysis result data is got average participation percentage in my cycle I is 42,56% and cycle II 74,47% happen student participation enhanced from my cycle to cycle ii as much as 25%. Inferential with card media can be increased class student participation IV country elementary school. Conection with watchfulness result that got above so as suggestion in increase student participation, teacher can use card media in study IPS